AB0779 Long term follow-up of a systemic sclerosis group treated with bosentan. (12th June 2018) - Groseanu, L.; Berghea, F.; Bojinca, V.; Balanescu, A.; Borangiu, A.; Mazilu, D.; Daia-Iliescu, S.; Opris-Belinski, D.; Saulescu, I.; Constantinescu, C.; Abobului, M.; Ionescu, R.
Abstract : Background: Prospective studies with Bosentan have shown short term efficacy, while it is not clear whether long-term treatment may be effective or whether ulcers may recur once treatment is discontinued. Objectives: Our objective was to evaluate the long term efficacy and tolerability of bosentan in patients with systemic sclerosis (SSc) who develop digital ulcers (DU). Methods: In the present prospective, observational, non-controlled study, we followed 26 SSc patients treated with Bosentan from Sept 2014 to Dec 2017 Number of DU, semiquantitative capillaroscopic scoring, VAS (visual analoque scale) for Raynaud, VAS for DU and HAQ were evaluated every 6 month. Results are presented as mean(sd). The difference between efficacy measures at follow-up visits was tested with the Wilcoxon's signed-rank test. Results: The group included 26 patients, 16 females, 11 diffuse subsets, age was 48.08 (9.8) years, disease duration was 84.35 (76.04) months, number of DU was 4.27 (3.71), most of them had a late scleroderma pattern pattern (16/26). Microangiopathy evolution score was 5.19 (2.04), VAS for DU was 75.52 (16.17), VAS for Raynaud was 67, 43 (14.16), HAQ was 1.62 (0.55). 5 patients received Bosentan less then 6 month, so they were excluded from the statistical analysis. 6 month evaluation revelead significant decrease in the number of DU (p<0.01), the VAS for DU (p<0.01), the VAS for Raynaud (p=0.03) and the HAQ (p=0.04), but not of the microangiopathy evolution score. No significant difference was noticed of the above mentioned parameters at the next follow-up evaluations. Regarding Bosentan safety: 6 patients died during the follow up (3 cases of severe pulmonary arterial hypertension, 1 scleroderma renal crisis, 1 heart failure, 1 post vascular surgery). Bosentan was stopped due to lack of efficacy in 2 case and due to side effects in 3 cases: 2 elevated liver enzymes, 1 severe trombocytopenia and 1 dyspneea agravation. 12 patients had a follow up after a 6 months Bosentan stop. We did not notice any significant increase in the number of DU, the VAS for DU or Raynaud, the capillaroscopic semiquantitative scoring or the HAQ. Conclusions: We noted a significant decrease in the number of DU, patients perception of Raynaud and of DU after 6 months of treatment and the effect was maintained in the 3 years follow-up, even 6 months after Bosentan was stopped. In this long-term follow-up no new unidentified adverse reactions were found, except for the unexpected severe thrombocytopenia. The present study is limited due to the small sample size, to the observational nature and should be viewed as descriptive. Questions rise about drug costs (6 months or long term treatment), but it also has to be emphasised that most of these lesions were chronic and nonresponsive to previous treatments. References: [1] Matucci-Cerinic M, et al.Bosentan treatment of digital ulcers related to systemic sclerosis: results from the RAPIDS-2 randomised, double-blind, placebo-controlled trial. Ann Rheum Dis. 2011;70(1):32–8 2] P. García de la Peña-Lefebvre, et al. Long-term experience of bosentan for treating ulcers and healed ulcers in systemic sclerosis patients. Rheumatology (Oxford). 2008;47(4):464–6. Disclosure of Interest: None declared